2013
DOI: 10.3897/natureconservation.4.3626
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Natura 2000 network to cover threatened species

Abstract: The world's biodiversity is currently in rapid decline -Europe being no exception -with as principal cause a human-mediated global change. The Natura 2000 network is an important conservation tool for European biodiversity; it is a network of natural and semi-natural sites within Europe with high heritage values due to the exceptional flora and fauna they contain. Here, we evaluated the coverage of 300 threatened species by the Natura 2000 network, and determined potential factors influencing the designation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 24 publications
3
64
0
Order By: Relevance
“…Protected areas vary widely between and within countries and regions, and the varying characteristics include the institution date, conservation focus, effective level of protection, permanence of protection, constancy of protection, ecological scale of protection, type of management, management authority and reference legislation, to cite some of them. In addition, the effectiveness of the selection process and the resulting Natura 2000 network have often been questioned because each country made its designations largely independently, and the designation of sites has been criticised as depending too strongly on governmental politics, economic and cultural criteria, and interactions between society and the environment Fenu et al, 2017;Gruber et al, 2012;Orlikowska et al, 2016;Trochet and Schmeller, 2013). In addition, in their analysis, Trochet and Schmeller (2013) demonstrated that the Natura 2000 network also covers species not listed in the annexes of the Habitats Directive, at least in the case of mammals, birds and reptiles; this might happen also for plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protected areas vary widely between and within countries and regions, and the varying characteristics include the institution date, conservation focus, effective level of protection, permanence of protection, constancy of protection, ecological scale of protection, type of management, management authority and reference legislation, to cite some of them. In addition, the effectiveness of the selection process and the resulting Natura 2000 network have often been questioned because each country made its designations largely independently, and the designation of sites has been criticised as depending too strongly on governmental politics, economic and cultural criteria, and interactions between society and the environment Fenu et al, 2017;Gruber et al, 2012;Orlikowska et al, 2016;Trochet and Schmeller, 2013). In addition, in their analysis, Trochet and Schmeller (2013) demonstrated that the Natura 2000 network also covers species not listed in the annexes of the Habitats Directive, at least in the case of mammals, birds and reptiles; this might happen also for plants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effectiveness of the selection process and the resulting Natura 2000 network have often been questioned because each country made its designations largely independently, and the designation of sites has been criticised as depending too strongly on governmental politics, economic and cultural criteria, and interactions between society and the environment Fenu et al, 2017;Gruber et al, 2012;Orlikowska et al, 2016;Trochet and Schmeller, 2013). In addition, in their analysis, Trochet and Schmeller (2013) demonstrated that the Natura 2000 network also covers species not listed in the annexes of the Habitats Directive, at least in the case of mammals, birds and reptiles; this might happen also for plants. Concerns also exist on the role of protected areas, in general, in providing effective biodiversity conservation (Geldmann et al, 2015;Le Saout et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that setting Natura 2000 sites is an effective conservation measure which also benefits nontarget species (EEA 2015). Trochet and Schmeller (2013) evaluated the coverage of 300 threatened species by the Natura 2000 network, and identified potential factors influencing the designation of sites and the structure of the network within a country (social, ecological and demographic national factors). The analysis was based on the coverage ratio between the Natura 2000 sites and distribution maps of threatened European species.…”
Section: Figure 1-1 the Natura 2000 Network For The Eu-28 Which Compmentioning
confidence: 99%
“…Hence, the coverage of the network for those groups is difficult to determine (Trochet and Schmeller 2013). Insufficient or outdated data is an important problem that appeared during site selection as well as on-going management deliberations and needs to be solved.…”
Section: Overallmentioning
confidence: 99%